Comparison of catastrophic out-of-pocket medical expenditure among older adults in the United States and South Korea: what affects the apparent difference? - Narae Kim; Mireille Jacobson (BMC, 2022)
Abstract Background Medical spending rises sharply with age. Even with universal health insurance, older adults may be at risk of catastrophic out-of-pocket medical spending. We aimed to compare catastrophic out-of-pocket medical spending among adults ages 65 and older in the United States, where seniors have near-universal coverage through Medicare, versus South Korea, where all residents have national health insurance. Methods We used the 2016 Health and Retirement Study and the Korean Longitudinal Study of Aging. The study population were adults ages 65 and over in the US (n = 9,909) and South Korea (n = 4,450; N = 14,359). The primary outcome of interest was older adults' exposure to catastrophic out-of-pocket medical expenditure, defined as out-of-pocket medical spending over the past two years that exceeded 50% of annual household income. To examine the factors affecting catastrophic out-of-pocket medical spending of older adults in both countries, we performed logistic regression analyses. To compare the contribution of demographic factors versus health system-level factors to catastrophic out-of-pocket medical spending, we performed a Blinder-Oaxaca decomposition. Results The proportion of respondents with catastrophic out-of-pocket medical expenditure was 5.8% and 3.0% in the US and South Korea, respectively. A Blinder-Oaxaca decomposition showed that the difference in the rate of catastrophic out-of-pocket medical expenditure spending between the two countries was attributable largely to unobservable system-level factors, rather than observed differences in the sociodemographic characteristics. Conclusions Exposure to catastrophic out-of-pocket medical spending is considerably higher in the US than South Korea. Most of the difference can be attributed to unobserved health system-level factors.